Responses of polar energy budget to regional sea surface temperature changes in extra-polar regions - Q. Wang; Y. Liu; L. Zhang; C. Zhou (Atmospheric Chemistry and Physics)
Surface temperature at polar regions not only is affected by local forcings and feedbacks but also depends on teleconnections between polar regions and low-latitude regions. In this study, the responses of the energy budget in polar regions to remote sea surface temperature (SST) changes are analyzed using a set of idealized regional SST perturbation experiments. The results show that the responses of the polar energy budget to remote sea surface warmings are regulated by changes in atmospheric energy transport, and radiative feedbacks also contribute to the polar energy budget at both the top of atmosphere (TOA) and the surface. Specifically, an increase in poleward atmospheric energy transport to polar regions results in an increase in surface and air temperature, and the corresponding Planck feedback leads to radiative warming at the surface and radiative cooling at the TOA. In response to sea surface warmings in most mid-latitude regions, poleward atmospheric energy transport to polar regions in the corresponding hemisphere increases. Sea surface warming over most tropical regions enhances the polar energy transport to both Arctic and Antarctic regions, except that an increase in the Indian Ocean's temperature results in a decrease in poleward atmospheric energy transport to the Arctic due to the different responses of stationary waves. The sensitivity of the Arctic energy budget to tropical SST changes is generally stronger than that of the Antarctic energy budget, and poleward atmospheric heat transport is dominated by dry static energy, with a lesser contribution from latent heat transport. The polar energy budget is not sensitive to SST changes in most subtropical regions. These results help to explain how the polar climate is affected by the magnitude and spatial pattern of remote SST change.